A ring‐based compensator IMRT system optimized for low‐ and middle‐income countries: Design and treatment planning study. Issue 7 (10th June 2018) - Van Schelt, Jonathon; Smith, Daniel L.; Fong, Nicholas; Toomeh, Dolla; Sponseller, Patricia A.; Brown, Derek W.; Macomber, Meghan W.; Mayr, Nina A.; Patel, Shilpen; Shulman, Adam; Subrahmanyam, G. V.; Govindarajan, K. N.; et al.
Abstract : Purpose: We propose a novel compensator‐based IMRT system designed to provide a simple, reliable, and cost‐effective adjunct technology, with the goal of expanding global access to advanced radiotherapy techniques. The system would employ easily reusable tungsten bead compensators that operate independent of a gantry (e.g., mounted in a ring around the patient). Thereby the system can be retrofitted to existing linac and cobalt teletherapy units. This study explores the quality of treatment plans from the proposed system and the dependence on associated design parameters. Methods: We considered 60 Co‐based plans as the most challenging scenario for dosimetry and benchmarked them against clinical MLC‐based plans delivered on a linac. Treatment planning was performed in the Pinnacle treatment planning system with commissioning based on Monte Carlo simulations of compensated beams. 60 Co‐compensator IMRT plans were generated for five patients with head‐and‐neck cancer and five with gynecological cancer and compared to respective IMRT plans using a 6 MV linac beam with an MLC. The dependence of dosimetric endpoints on compensator resolution, thickness, position, and number of beams was assessed. Dosimetric accuracy was validated by Monte Carlo simulations of dose distribution in a water phantom from beams with the IMRT plan compensators. Results: The 60 Co‐compensator plans had on average equivalent PTV coverage and somewhat inferior OAR sparing compared to the 6 MV‐MLC plans, but the differences in dosimetric endpoints were clinically acceptable. Calculated treatment times for head‐and‐neck plans were 7.6 ± 2.0 min vs 3.9 ± 0.8 min (6 MV‐MLC vs 60 Co‐compensator) and for gynecological plans were 8.7 ± 3.1 min vs 4.3 ± 0.4 min. Plan quality was insensitive to most design parameters over much of the ranges studied, with no degradation found when the compensator resolution was finer than 6 mm, maximum thickness at least 2 tenth‐value‐layers, and more than five beams were used. Source‐to‐compensator distances of 53 and 63 cm resulted in very similar plan quality. Monte Carlo simulations suggest no increase in surface dose for the geometries considered here. Simulated dosimetric validation tests had median gamma pass rates of 97.6% for criteria of 3% (global)/3 mm with a 10% threshold. Conclusions: The novel ring‐compensator IMRT system can produce plans of comparable quality to standard 6 MV‐MLC systems. Even when 60 Co beams are used the plan quality is acceptable and treatment times are substantially reduced. 60 Co‐compensator IMRT plans are adequately modeled in an existing commercial treatment planning system. These results motivate further development of this low‐cost adaptable technology with translation through clinical trials and deployment to expand the reach of IMRT in low‐ and middle‐income countries.